Controlled Solidification of Dilute Binary Iron-Nickel Alloys - Jin, Iljoon (My University, 1972)
This thesis is concerned with establishing an improved theoretical and experimental description of the steady state controlled solidification of dilute binary alloys. In the present theory, a mathematical model is developed to describe an experimental situation in which alloy solidification is controlled by solute diffusion in the liquid phase. The theory gives a unique solution of the solute diffusion equation and predicts the variation of the thermodynamic properties at the solid-liquid interface, particularly at the dendrite tip, as a function of material constants and growth parameters. An experimental program was developed to investigate the dependence on the growth parameters of the morphological development of the interface and the concentration variations at the interface of an Fe-8 wt. Ni alloy. Experimental results for this particular system can be successfully rationalized by the approximate solution of the present theory.
Keywords: Materials Science and Engineering; Metallurgy; Materials Science and Engineering